Corrosion simulation of automotive materials under exposure in biodiesel - Cetin, S.Y.; M. A., Maleque; Haji Hassan, Masjuki; Adib, Hamdani; Rahman, Md Mustafizur
Biodiesel being an eco-friendly and renewable alternative fuel has gained attention due to its clean nature. However, the corrosion behaviour of automotive component materials in the presence of biodiesel is well known. Therefore, a computational fluid dynamics simulation on corrosion phenomena of automotive component materials has been done under exposure of biodiesel over varying time intervals. Two different types of steel materials (carbon steel and stainless steel) were chosen for the simulation of corrosion under biodiesel exposure. However, the corrosion was predominantly observed in both carbon steel and stainless steel materials. A notable finding emerged as stainless steel demonstrated significantly superior corrosion resistance compared to carbon steel when subjected to biodiesel-induced corrosion. Furthermore, the corrosion resistance of both stainless steel and carbon steel was found to be within the acceptable range for utilising biodiesel in automotive engines. This finding underscores the viability of biodiesel as a sustainable and viable alternative fuel for the automotive industry